EAU Guidelines on Chronic Pelvic Pain - Fall, Magnus; Baranowski, Andrew P.; Elneil, Sohier; Engeler, Daniel; Hughes, John; Messelink, Embert J.; Oberpenning, Frank; de C. Williams, Amanda C. (European urology, 2010)
These guidelines were prepared on behalf of the European Association of Urology (EAU) to help urologists assess the evidence-based management of chronic pelvic pain (CPP) and to incorporate the recommendations into their clinical practice. To revise guidelines for the diagnosis, therapy, and follow-up of CPP patients. Guidelines were compiled by a working group and based on a systematic review of current literature using the PubMed database, with important papers reviewed for the 2003 EAU guidelines as a background. A panel of experts weighted the references. The full text of the guidelines is available through the EAU Central Office and the EAU Web site (www.uroweb.org). This article is a short version of the full guidelines text and summarises the main conclusions from the guidelines on the management of CPP. A guidelines text is presented including chapters on chronic prostate pain and bladder pain syndromes, urethral pain, scrotal pain, pelvic pain in gynaecologic practice, neurogenic dysfunctions, the role of the pelvic floor and pudendal nerve, psychological factors, general treatment of CPP, nerve blocks, and neuromodulation. These guidelines have been drawn up to provide support in the management of the large and difficult group of patients suffering from CPP. The treatment of chronic pelvic pain (CPP) continues to present a number of challenges with regard to understanding its aetiology and to its management. Basic investigations must be undertaken to rule out “well-defined” pathologies. If the results are negative, a well-defined pathology is unlikely. Further investigations should be done only for specific indications (eg, for subdivision of a pain syndrome). Research based on robust clinical parameters is needed to further an evidence-based approach to the treatment of CPP.